1985
DOI: 10.1080/00021369.1985.10866862
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Synthesis of Adenine Arabinoside

Abstract: The microbiological synthesis of 9-p-D-arabinofuranosyl adenine (ara-A, an antiviral drug) from adenine and arabinofuranosyluracil (ara-U) is described. Various bacteria, especially Enterobacter aerogenes. Escherichia coli, Erwinia herbicola and Aeromonas salmonicida, were found to be able to transfer the arabinofuranosyl moiety of ara-U to adenine (transarabinosylation) in the presence of inorganic phosphate. The optimum conditions for the transarabinosylation were pH 7.0 and 60°C. No reaction was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…The overall result of nucleoside phosphorylase catalysis is the transfer of the ribose or the deoxyribose moiety of a readily available nucleoside to different purine or pyrimidine nucleobases or analogs thereof through the intermediacy of R-1-P. These transformations have either been accomplished by employing isolated enzymes (16) or whole cells of microorganisms containing high percentages of the required enzyme (17)(18)(19)(20)(21). The deleterious effect of the other enzymes present in whole cells can be neutralized by conducting the reactions at 60ЊC, a temperature at which the nucleoside phosphorylases maintain more than 70% of their activities (22,23).…”
Section: Glycosyl Transfer Reactions Catalyzed By Nucleoside Phosphormentioning
confidence: 99%
See 1 more Smart Citation
“…The overall result of nucleoside phosphorylase catalysis is the transfer of the ribose or the deoxyribose moiety of a readily available nucleoside to different purine or pyrimidine nucleobases or analogs thereof through the intermediacy of R-1-P. These transformations have either been accomplished by employing isolated enzymes (16) or whole cells of microorganisms containing high percentages of the required enzyme (17)(18)(19)(20)(21). The deleterious effect of the other enzymes present in whole cells can be neutralized by conducting the reactions at 60ЊC, a temperature at which the nucleoside phosphorylases maintain more than 70% of their activities (22,23).…”
Section: Glycosyl Transfer Reactions Catalyzed By Nucleoside Phosphormentioning
confidence: 99%
“…Whole cells of various bacteria (including Enterobacter aerogenes, Escherichia coli, Erwinia herbicola, and Aeromonas salmonicida), containing high percentage of nucleoside phosphorylase are capable of transferring the arabinofuranosyl moiety from arabinofuranosyluracil to adenine (17). Kalinichenko et al (35) have used a suspension of glutaraldehyde treated E. coli BM-11 cells in potassium phosphate solution for the synthesis of an anti-herpes drug, brivudin [(E )-5-(2-bromovinyl)-2Ј-deoxyuridine] using 2Ј-deoxyguanosine or thymidine as glycosyl donor and (E )-5-(2-bromovinyl)uracil as the acceptor.…”
Section: Scheme 2 Schemementioning
confidence: 99%
“…In the absence of induction, the specific activity of UPase from E. aerogenes towards Ara-U is only one-tenth that towards uridine, which may account for the longer time required for UPase and PNPase to catalyze the synthesis of Ara-A compared to the synthesis of natural nucleosides. The shortest synthesis time reported for Ara-A is about 15 h (Utagawa et al, 1985). Here, we show that induction of E. aerogenes by cytidine or CMP greatly enhances the efficiency of the Ara-A reaction, dramatically reducing the enzymatic reaction time from 36 h to 6 h. Thus, the induction of cells grown in a nutrient medium represents a simple and effective way to enhance the activities of NPases.…”
Section: Discussionmentioning
confidence: 87%
“…The enzymatic synthesis of Ara-A has been extensively studied (Krenitsky et al, 1979;Utagawa et al, 1985;Ling et al, 1990;Giuseppina et al, 2000), and showed capability of producing high substrate conversion rates and a high yield of final product. However, the enzymatic approach used to produce Ara-A is slower compared to the rate of natural nucleosides production.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant wet cell paste was used as catalyst of the reaction [2] after suspending in phosphate buffer (5 ml) and addition of the nucleoside and purine base. The mixture was stirred and heated at constant temperature in glycerin bath and the reaction products were analyzed by tlc and hplc.…”
Section: Methodsmentioning
confidence: 99%